Ethnomathematics exploration of Jember Fashion Carnaval (JFC) costume design - Bashar, Nazarul; Sujiwo, Dimas Anditha Cahyo; Anas, Aswar (International Journal of Trends in Mathematics Education Research, 2023)
Knowledge and views of certain tribes, community groups, or individuals without going through formal education. Mathematics with cultural nuances (ethnomathematics) will make a huge contribution to mathematics learning. The aim of this research is to describe the mathematical concepts contained in JFC costume designs. In this research, researchers used qualitative research with an ethnographic approach. The instrument in this research is a human instrument; the researcher is directly related to the research and acts as a data collector through library data collection, interviews, observation, and documentation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. The results of this research show that ethnomathematics in Jember Fashion Carnival (JFC) fashion design can be in the form of the concept of symmetry and flat shapes such as triangles, squares, rhombuses, and circles. This can be seen in several costumes worn at JFC. The ethnomathematics in JFC costumes can certainly provide inspiration for educators to develop interesting learning by applying ethnomathematics. Educators can use JFC costume design patterns as material for teaching students mathematical concepts.